Kualitas Pelayanan Penduduk Lanjut Usia pada Komda Lansia Kabupaten Wonosobo - Puspita Fibriani; Ari Subowo (Journal of Public Policy and Management Review, 2017)
Government as a public servant should also seek to participate in improving service quality. Government efforts in providing services, especially to elderly population with the establishment of Komda Lansia. Increasing the elderly population will surely have an impact on the intensity of services provided by the Komda Lansia. The quality of Komda Lansia service in providing services to the elderly can be known based on the performance level of Komda Lansia in providing services. This research was conducted at Komda Lansia, District Wonosobo, Central Java. This study aims to determine the quality of elderly service in Komda Lansia in District Wonosobo, so it can be known what factors inhibit elderly service at Komda Lansia in District Wonosobo. The sample used is as many as 47 respondents, with the technique of sampling using technique Purposive Sampling. Data analysis using Important Performance Analysis (IPA). The service quality variables are performance level (X) and level of interest / expectation of elderly (Y), with service quality dimension are Reliability, Responsiveness, Assurance, Empathy, Tangible. The results of the study based on the Rating of Interest and Performance of Quality of Service, that the value for the average performance appraisal is 1.73 and the interest rating of 1.77. The value of interest is greater than the value of performance. This indicates a gap between services received by the elderly in the hope of the elderly. Based on Average Assessment Level of Interest and Level of Performance and Customer Gap Based on Service Quality Dimension, dimension Reliability occurs positive gap with average 0,006, dimension Response happened negative gap with average -0,073, dimension Assurance happened negative gap with average -0,150, Empathic dimension occurs negative gap with average -0,135, physical shape dimension happened positive gap with average 0,245. It can be said that the factors that inhibit the service is on the dimensions of Response, Assurance, and Empathy. It is this factor that needs to be improved to improve the Komda Lansia service of District Wonosobo.